Motivasi Konsumen Remaja Surabaya dalam Menggunakan Tiktok Live Video Shopping - Sastrina Happy Dwi Amara; Ahmad Zamzamy (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Teenagers are the top consumer group and a potential market for the online retail sector. Teenagers are the age group that adopts technology the fastest, so they stand to gain the most from the availability of online shopping sites. This study was created by adapting earlier research that was done on live shopping broadcasts or live video shopping by Ma, Andersson, and Pitz in 2021. Both studies attempt to explain why viewers are devoted to particular channels by putting forth three types of connected consumer gratification in live shopping broadcasts. Hedonic motivation, utilitarian motivation, and social motivation are three different types of gratification. The method used in this study is descriptive qualitative. Data collection techniques start from data collection, data reduction, data presentation, and conclusions. From seven informants of high school / K students in the city of Surabaya. The results show that in the utilitarian motivation of Surabaya adolescent consumers get information and product picture more clearly thanks to live shopping broadcasts. On hedonic motivation, sellers on the direct shopping channel became the main factor that led to entertainment satisfaction during watching the live shopping channel. While social motivation in Tiktok LVS has a small role for Surabaya teenagers in using Tiktok LVS. Social interaction between seller-buyer is not an important issue regarding the audience's motivation to engage in watching certain channels on Tiktok LVS. Keywords: Online shop, consumer satisfaction, Tiktok Live Video Shopping